Long-Term Surveillance and Life-Time Care for Pediatric Patients Suffering from Hydrocephalus - Krause, Matthias; Merkenschlager, Andreas; Mahr, Cynthia Vanessa; Bernhard, Matthias K.; Kasper, Ekkehard M.; Weißer, Margit; Wachowiak, Robin (Journal of Pediatric Neurology, 2020)
Even though shunt surgery has been an established and widely accepted treatment for congenital hydrocephalus for five decades, long-term follow-up and functional outcome data are scarce. Based on our experience, we advocate a very rigid follow-up regimen throughout life for every hydrocephalus patient encountered with individual screening intervals not longer than 1 year in childhood and adolescence and surveillance intervals of 2 years in adulthood. A continuous treatment of the patients at the primary institution that performed hydrocephalus surgery provides an optimal setting to be prepared for the detection of adverse events of shunt malfunctioning. However, some patients may still encounter catastrophic events resulting in persistent deficits or death.
Keywords: hydrocephalus; long-term outcome; transition; follow-up